GAMBARAN PENGETAHUAN, UMUR,DUKUNGAN SUAMI, DAN EKONOMI, PADA IBU HAMIL TENTANG KEPATUHAN PEMERIKSAAN KLINIK PRATAMA SANTA ELISABETH MEDAN - Lilis Sumardiani (STIKes Santa Elisabeth Medan, 2020)
Introduction :antenatal care is an examination of pregnant women both physically and mentally as well as saving mothers and children in pregnancy, childbirth and the puerperium, so that they post partum healthy and normal not only physically but also mentallyMethod : The study was conducted by distributing questionnaires to pregnant women with emesis gravidarum. Data analysis using univariants for frequency distribution. Result : The results showed an overview of knowledge of pregnant women with good knowledge of 13 people (65%), sufficient knowledge of 5 people (25%) and lack of knowledge of 1 person (5%) while lacking knowledge of pregnant women who did not comply did 1 pregnancy check up (5) %). overall obedient pregnant women undergo pregnancy examinations aged <20 years 7 people (35%), 20-30 years there are 7 people (35%) and there are 4 people> 35 years (20%). while those aged <20 years who are not compliant pregnant women do pregnancy examinations 2 people (10%). pregnant women about compliance with antenatal care namely, support from the husband is very good there are 12 people (60%), good 4 people (20%) and enough 4 people (40%). 20%), the middle economy there are 13 people (65%), and the low economy 4 people (20%), while the economy is lacking in pregnant women who do not comply with one pregnancy checkup (5%). parity, shows that the total number of pregnant women regarding compliance with antenatal care is, that has children who live 1 times 4 people (20%), the number of children who live 2-5 times 11 people (55%), and the number of children who live> 5 times 5 people (25%) while parity, in pregnant women who do not comply with pregnancy examination 1 person (5%) Duscussion:From this study it can be concluded that knowledge, age, husband support, economy and parity in pregnant women regarding compliance with antenatal care in the Klinik Pratama Santa Elisabeth Medan is said to be a minority who are disobedient and more who are obedient do ANC visits